The Relation Between Outside Patient Knowledge with Compliance Use of Mask COVID-19 Preventive Effort at Technical Implementation Unit Besiq Public Health Centre, West Kutai Regency - Pujiarto, Anang (Rifa'Institute, 2023)
Introduction: The COVID-19 pandemic has hit the world, including Indonesia. Knowledge and compliance with the use of masks is one way to prevent the spread of COVID-19. Objective: This study aims to determine the relationship between knowledge and ompliance to the use of masks at Pusat Kesehatan Masyarakat Besiq, West Kutai. Method: Quantitative research with analytic study and cross-sectional design A sample of 97 people uses purposive sampling technique. Results and Discussion: Of the 97 respondents most of them have high knowledge of COVID-19, namely 83 respondents (85.6%), and a small proportion of low knowledge (14.4%), most of the respondents obeyed using masks, 80 respondents (82.5%) and small of proportion are not compliant 17 respondents (17.5%). Based of the Chi-Square test, the significance of p between the independent variables knowledge and the dependent variable compliance with the use of masks was 0.000 (p <0.05), the result that there is a relation relationship between knowledge and compliance use of masks. Conclusion: There is a relation between knowledge and compliance to the use of masks. It is recommended that the Pusat Kesehatan Masyarakat continue to improve health services in making policy on COVID-19 prevention programs during the pandemic